1992
DOI: 10.1177/001440299305900305
|View full text |Cite
|
Sign up to set email alerts
|

Educational Services for Children with Chronic Illnesses: Perspectives of Educators and Families

Abstract: Two parallel studies examined schools' and families' perceptions of the needs of children with chronic illnesses. Samples of 80 California school districts and 72 families were interviewed regarding types of chronic illnesses and school services, perceptions of and barriers to services, strategies for overcoming barriers, and fears and concerns of children with chronic illnesses. Most students were served in regular classes or at home. The most common barriers named by districts were funding and lack of public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 5 publications
0
27
0
2
Order By: Relevance
“…For many of these children, hospital treatments save their lives while unintentionally compromising attention, memory, fatigue, visual scanning, and spatial abilities (Thies, 1999). In one study, 45% of students experiencing chronic illness performed below their peer comparisons and many reported that they disliked school (Lynch, Lewis, & Murphy, 1992). Given that illness and frequent and/or extended hospitalizations impair a child's participation in school, educational interventions become an essential component toward supporting this student population (Kaffenberger, 2006); though, as Thies (1999) asks, "Who is responsible for managing the education of […] children and adolescents with chronic illness?"…”
Section: Introductionmentioning
confidence: 99%
“…For many of these children, hospital treatments save their lives while unintentionally compromising attention, memory, fatigue, visual scanning, and spatial abilities (Thies, 1999). In one study, 45% of students experiencing chronic illness performed below their peer comparisons and many reported that they disliked school (Lynch, Lewis, & Murphy, 1992). Given that illness and frequent and/or extended hospitalizations impair a child's participation in school, educational interventions become an essential component toward supporting this student population (Kaffenberger, 2006); though, as Thies (1999) asks, "Who is responsible for managing the education of […] children and adolescents with chronic illness?"…”
Section: Introductionmentioning
confidence: 99%
“…While a greater proportion of students with complex health care needs also have disabilities requiring special education services, not all children with complex health care needs have special educational needs as defined by PL 94-142 (Council for Exceptional Children, 1988). In a recent study of a sample of school districts in California, Lynch, Lewis and Murphy (1992) reported that, on the average, only 31 % of the students in their district who were considered to have chronic illnesses were identified as having special education needs. Eightyfive percent of these students were in regular educational classrooms and received no special educational services.…”
Section: How Did We Get Here?mentioning
confidence: 99%
“…Sometimes home stays are not long enough to meet the minimum-day criteria; absences may be brief, but frequent enough to disrupt education. Students with complex health care needs require flexible systems, ones that can adjust to the frequently changing educational needs of the students (Lynch, Lewis, & Murphy, 1992).…”
Section: "How Do I Teach Him?"mentioning
confidence: 99%
“…In the case of children with chronic renal failure specifically, the dearth of research on issues of hospital-school liaison -and issues of educational provision at large -has been particularly pronounced. Furthermore, the relatively few existing studies (completed in the UK and the USA) addressing educational issues in children with chronic medical conditions have investigated mainly the perspectives of the children, their parents and their teachers, whereas the views of health professionals -key people involved in the children's lives and care -are largely missing (Asprey and Nash, 2006;Bolton, 1997;Chacraborty and Hamer, 2005;Everett and Fulton, 2002;Harris and Farrell, 2004;Lynch et al, 1992;McCann et al, 2002;Mukherjee et al, 2000Mukherjee et al, , 2002Norris and Closs, 2003). This suggests a particular need for further research investigating health professionals' perspectives on the education of children with chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%